Yvan Goll ed il crollo del mito d'Europa - Terigi, Elisabetta (Premio Ricerca «Città di Firenze», 2013)
The objective of this work is to investigate the meaning of myth in the work of Yvan Goll (1891-1950), a Franco-German, bilingual and Jewish poet. In his poems, characters of the classical tradition alternate with biblical and historical figures: among all stands out the topic of the myth of Europe, understood as a geographical space and universal homeland for all those who, born in a borderland like Goll, feel "heimatlos", that is stateless. The aim of the thesis is to demonstrate how the artist's dialogue with the myth follows precise and constant rules with a clear goal: to send a strong message to the contemporary world. Taking into consideration the works dedicated to the mythical heritage, it is observed how after the Mythisierung (mythisation) of the old continent, the author deconstructs his own creation through a systematic Entmythisierung (demythisation).